Dentistry with a vision building a rewarding practice and a balanced life - Kendall, Gerald I.; Wadhwa, Gary S. (Hanover Park, IL : Quintessence Publishing Co, Inc., 2019)
Written as a novel, this book models a real-life story about how a dentist improved his practice from a loss to over
Dentistry with a vision : building a rewarding practice and a balanced life -- TABLE OF CONTENTS -- PREFACE -- ACKNOWLEDGMENTS -- One: Just Another Day in Crisis: Dealing with Staff Challenges -- Two: A Tough Call: Spending Money to Make Money -- Three: No Time for an Emergency: Identifying Scheduling Problems -- Four: The Intervention: Learning from Mistakes -- Five: The First Lesson: Making Investment and Financial Decisions -- Six: The $100,000 Day: Applying New Principles -- Seven: A Difficult Beginning: Learning Step 1 of the Five Focusing Steps -- Eight: The 2Aha3 Moment: Grasping the Rest of the Five Focusing Steps -- Nine: Deal or No Deal: Understanding Patients' Six Layers of Resistance -- Ten: Harvesting the Gold: Beginning the Dental Sales Process -- Eleven: Help Wanted: Hiring a Salesperson -- Twelve: A New Plateau: The Dentist As Constraint -- Thirteen: The Working Vacation: Learning to Be Lean -- Fourteen: Quality Time: Simplifying Six Sigma -- Fifteen: Working with the Clock: A Lesson in Scheduling -- Sixteen: Hard Science on the Softer Side of Business: Managing People -- Seventeen: One Year Later: Profits for a Purpose -- Appendix a. Vision Tree for a Dental Practice -- Appendix b. Step-by-Step Success in Dental Practice.
Includes bibliographical references and index.
Keywords: Practice Management, Dental -- organization & administration; Efficiency, Organizational; Practice Management, Medical -- economics